Increased hs-CRP and Sepsis Influence the Occurrence of Thrombocytopenia in Severe and Critically Ill COVID-19 Patients Receiving Anticoagulants - Ami Ashariati Prayoga; Siprianus Ugroseno Yudho Bintoro; Pradana Zaky Romadhon; Muhammad Noor Diansyah; Putu Niken Ayu Amrita; Merlyna Savitri; Choirina Windradi; Krisnina Nurul Widiyastuti (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Despites its benefits, as one of COVID-19 principal treatments, anticoagulant raises a significant concern regarding the anticoagulant-related thrombocytopenia. However, up to date, there is lack of study examining anticoagulantinduced thrombocytopenia during COVID-19, hence this study was conducted to determine the factors inducing anticoagulant-induced thrombocytopenia in COVID-19 patients.METHODS: An observational cross-sectional study of 106 anticoagulant-treated COVID-19 subjects was conducted. Blood serum was drawn from subjects, then platelets, prothrombin time (PT), activated partial thromboplastin (aPPT), international ratio (INR), D-dimer, ferritin, fibrinogen, and high-sensitivity C-reactive protein (hs-CRP), were measured. For thrombocytopenia risk assessment, the 4T score was calculated. To assess the risk of thrombocytopenia. Statistical analysis using Chi-square and Mann-Whitney U test were performed and followed by multivariate analysis to examine the correlation among the thrombocytopenia risk factors.RESULTS: Significant differences were identified in the length of stay (LOS) (p=0.04), disease severity (p=0.021), sepsis (p=0.006), hs-CRP (p=0.003), and mortality rate (p=0.028) between thrombocytopenia and nonthrombocytopenia groups. A multivariate analysis through linear and logistic regression disclosed an increase in hs-CRP (OR=-0.29; p=0.045) and sepsis (OR=4.32; p=0.03) that precipitate the thrombocytopenia events.CONCLUSION: In severe and critically ill COVID-19 patients, the occurrence of thrombocytopenia was followed by an increase in inflammatory parameters such as D-dimer, fibrinogen, ferritin, hs-CRP and prolonged coagulation. The increase in hs-CRP and sepsis may raise the risk of thrombocytopenia, especially in severe and crtically ill cases of COVID-19.KEYWORDS: COVID-19, anticoagulant, thrombocytopenia, inflammation, infectious disease